2019
DOI: 10.1016/j.bbrc.2019.04.123
|View full text |Cite
|
Sign up to set email alerts
|

ATP turnover and glucose dependency in hematopoietic stem/progenitor cells are increased by proliferation and differentiation

Abstract: Hematopoietic stem cells (HSCs) are quiescent cells in the bone marrow niche and are relatively dependent on glycolytic ATP production. On the other hand, differentiated cells, including hematopoietic progenitor cells (HPCs), preferentially generate ATP via oxidative phosphorylation. However, it is unclear how cellular differentiation and the cell cycle status affect nutritional requirements and ATP production in HSCs and HPCs. Using a newly developed culture system, we demonstrated that survival of HPCs was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“… 56 , 57 Activated HSCs increase the demands for ATP and further decrease their ATP level. 58 Apoptosis is a form of well-programmed cell death by forming apoptotic bodies, and it requires energy to complete this progress. 59 , 60 GSDME-mediated pyroptosis is a kind of necrosis, 34 and might demand little or no energy.…”
Section: Discussionmentioning
confidence: 99%
“… 56 , 57 Activated HSCs increase the demands for ATP and further decrease their ATP level. 58 Apoptosis is a form of well-programmed cell death by forming apoptotic bodies, and it requires energy to complete this progress. 59 , 60 GSDME-mediated pyroptosis is a kind of necrosis, 34 and might demand little or no energy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we observed that the ATRA-driven NB4 granulocytic differentiation depends both upon glycolysis and OXPHOS for ATP production; however, the relative contribution of glycolysis increases in a time-dependent manner during the process of maturation. Differentiated hematopoietic cells, including hematopoietic progenitor cells and granulocyte/monocyte progenitors, although generating ATP preferentially via OXPHOS, strongly rely on ATP produced by glycolysis [126]. This commitment to the Warburg metabolism may support the notion that the mitochondrial functions related to ATP production is reduced in granulocytes, mitochondria being primarily involved in maintaining the redox balance and promoting flux through the glycolytic pathway while avoiding commitment to the apoptotic process [127].…”
Section: Discussionmentioning
confidence: 78%
“…Glucose is involved in the production of ATP within cells by glycolysis and the tricarboxylic acid cycle 34 . Therefore, we investigated the changes in intracellular ATP levels in both Cd‐treated HK‐2 cells and SLC2A4 ‐knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose is involved in the production of ATP within cells by glycolysis and the tricarboxylic acid cycle. 34 Therefore, we F I G U R E 3 Effect of SLC2A2 expression on the sensitivity of HK-2 cells to Cd. A, SLC2A2 mRNA levels in HK-2 cells treated with Cd for 6 hours were examined by real-time RT-PCR.…”
Section: Atp Levels and CD Toxicitymentioning
confidence: 99%